CRITICAL THINKING CHARACTERISTICS OF SMPN 14 PALU STUDENTS IN SOLVING GEOMETRY PROBLEMS BASED ON GENDER - Kadek Widiastuti; Sukayasa Sukayasa; Dasa Ismaimuza (USN Kolaka, 2024)
The aim of this research is to describe the critical thinking characteristics of male and female students in solving geometric problems. The type of research used in this research is qualitative research, because this research aims to describe and analyze phenomena or events individually or in groups. The approach used is a qualitative descriptive approach, because the results of this research are in the form of descriptions, namely descriptions in the form of words or sentences regarding the characteristics of students' critical thinking in solving geometry problems based on gender. Improving critical thinking skills in mathematics learning is very necessary because critical thinking and mathematics are an inseparable unit. The results of this research show that the critical thinking characteristics of subjects in solving geometric problems are: (a) in the clarification category, MA and FN subjects can formulate problems and appropriate information to solve problems precisely and clearly (b) in the assessment category (assessment) MA and FN subjects tried to collect relevant information, but MA identified the problem incorrectly (c) In the inference category, MA and FN subjects made wrong conclusions. (d) In the strategies category, MA subjects do not propose other alternatives, while FN subjects propose other strategies or alternatives when solving problems.